The Influence Of Service Quality And Motivation On The Performance Of Balerejo Village Officials, Dempet District, Demak Regency - Y.R. Satato; Syamsul Hadi; Tegar Pratama (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research was conducted in Balerejo Village, Dempet District, Demak Regency, with the aim of this study is to find out (1) the influence of service quality on performance, (2) the influence of motivation on performance, (3) the influence of service quality and motivation on performance, and (4) which variables have the most effect on performance.The number of samples used as many as 60 people as village officers / devices, with data collection techniques through questionnaires and observations, while data processing and analysis techniques using validity, reliability, multiple linear regression analysis, determination coefficients and hypothesis tests.The results showed that (1) service quality variables have a significant effect on performance, (2) significant motivation variables on performance (3) service quality variables and motivation simultaneously have a significant effect on performance, and (4) service quality variables are the most significant variables affect performance performance.